The effect of COVID‐19 on surgical management of skin cancers of the head, face and neck in elderly patients. Issue 2 (28th March 2023) - Borg, Tiffanie‐Marie; Eisold, Jessica; Miyanjo, Yusuf; Pappa, Elena
Abstract: Background: The Corona Virus (COVID‐19) has had a profound impact on healthcare systems worldwide, with interruptions to medical practices including the delivery of cancer treatment. Skin cancer is one of the leading causes of malignancy worldwide, with later stages of disease correlating to poorer prognosis. Immunocompromized and elderly patients represent populations that are at higher risk for adverse outcomes related to skin cancer, treatment delay and COVID‐19 infection. Methodology: Patients aged 65 and above who underwent surgical management of skin cancers from 31 January 2020 to 31 January 2021 were included in this study then compared with samples pre‐ and post‐pandemic. Retrospective analysis was performed regarding: date of referral to date of surgery, skin cancer type, location of cancer, surgery performed, anaesthesia used, sutures used and outcomes. Data was compared to national guidelines. Results: Five hundred and twenty skin cancers were included in this analysis, of which 340 were treated during the COVID‐19 pandemic. Of the cohort treated during the pandemic, 44.2% ( n = 111) received excision and direct closure, 13.1% ( n = 33) underwent reconstruction by integra dermal substitute, 3.2% ( n = 8) by split thickness skin graft, 6.4% ( n = 16) by full thickness skin grafts and 33.1% ( n = 83) by local flaps. Complete excision was achieved in 88.5% of cases ( n = 301). The mean time from referral to surgery was 119 days. There were no deaths associated with COVID‐19. Conclusion: Safe and prompt treatment of head and neck skin cancers is achievable despite the COVID‐19 pandemic. Measures to minimize infection risk include the use of teledermatology, reliable COVID‐19 testing, Green Pathways and a reduction in the mean referral to surgery time.